Changes in body weight and composition, metabolic parameters, and quality of life in patients with type 2 diabetes treated with subcutaneous semaglutide in real-world clinical practice - Pantanetti, Paola; Cangelosi, Giovanni; Alberti, Sara; Di Marco, Sandra; Michetti, Grazia; Cerasoli, Gianluca; Di Giacinti, Marco; Coacci, Silvia; Francucci, Nadia; Petrelli, Fabio; Ambrosio, Giuseppe; Grinta, Roberto (Frontiers in Endocrinology, 2024)
Subcutaneous once-weekly (ow) semaglutide is a recent treatment option for type 2 diabetes (T2D) and obesity, but real-world data on weight loss and associated changes in body composition, nutrients intake, and quality of life are still scarce.This observational, prospective clinical study involved all T2D patients starting ow semaglutide according to routine care between December 2021 and February 2022. Clinical information was collected after 6 months (T6) and 12 months (T12) from semaglutide initiation (T0). Bioelectrical Impedance Analysis (BIA) was performed to measure changes in body composition. Diabetes Treatment Satisfaction Questionnaire (DTSQ) and the 36 -items Short Form Health Survey (SF-36) were administered as patient-reported outcomes (PROs). Changes in continuous endpoints (weight, body composition, nutrients intake, other clinical parameters, and PROs) were assessed using mixed models for repeated measurements.Overall, 90 patients (age 63.0±10.0 years; diabetes duration 7.6±5.9 years; 58.9% men; HbA1c 7.7±1.1%; weight 95.4±19.4 Kg, BMI 34.6±6.4 Kg/m 2 ; 36.7% naïve to diabetes treatment, 43.3% on metformin, 10.0% on dual oral therapy, and 10.0% treated with schemes including insulin) were included in the study. After 6 months from semaglutide initiation, body weight significantly decrease by -4.69 Kg (95%CI -6.19;-3.19) (primary endpoint). After 12 months, body weight was further reduced (-5.38 Kg; 95%CI -7.79;-2.97). At BIA, fat mass was significantly reduced by 2.1 Kg after 6 months but only slightly reduced after 12 months vs. baseline; lean mass was also significantly reduced by over 3 Kg both at 6 and 12 months. Intake of all nutrients declined in the first 6 months of therapy, although only lipids reduction reached the statistical significance (-6.73 g; p=0.02).Statistically significant improvements in BMI, waist circumference, glycemic control, blood pressure and lipid profile were documented. Satisfaction with treatment (DTSQ questionnaire) and mental health (MCS score of SF-36 questionnaire) significantly increased during the follow-up.The study documented real-world benefits of semaglutide for treating obesity in T2D subjects, with important changes on clinical and patient-reported outcomes. Loss of lean mass associated with weight loss warrants attention; parallel strategies to preserve skeletal muscle and improve physical function, i.e. nutritional education and structured exercise, are of great importance.